The x coefficient is 2
Take half of 2 to get 2/2 = 1
Square 1 to get 1^2 = 1
Add and subtract 1 to the expression. This is the same as adding 0.
x^2 + 2x + 2
x^2 + 2x + 2 + 0
x^2 + 2x + 2 + (1-1)
(x^2 + 2x + 1) + 2 - 1
(x+1)^2 + 1
Answer: (x+1)^2 + 1
The first one would be 120 the second one would be 68
Answer:
school is a problem
Step-by-step explanation:
Have a great day!!!
The answer is x2<span> – 2</span>x<span> – 9 and that is option C</span>
Answer:
Step-by-step explanation:
First use distributive property: a(b + c) = a*b + a*c
3n - 6 = -8(6 + 5n)
3n - 6 = 6 * (-8) + 5n *(-8)
3n - 6 = -48 - 40n
Now add 40n to both sides
3n - 6 + 40n = -48 - 40n + 40n
43n - 6 = -48
Now add 6 to both sides
43n - 6 + 6 = -48 + 6
43n = -42
n = -42 /43